Тheoretical generalization of approaches to the definition of the nature of service: marketing and logistics aspect - Tan’kov, Kostyantyn; Starynets, Olena (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2016)
The paper considers theoretical approaches to determining the nature and content of the concept of service. It is shown that in the conditions of development of market relations there is a shift of attention of the enterprises in questions of production maximization to the formation of its high quality service support, which is considered as a determining factor of its effective market activity. The general methodological approach to the establishment of the concept of «service provision», based on the principles of marketing and logistics integration, is suggested.